Public Communication in Collaborative Public Management for Blue Economy Governance in Pangkajene and Kepulauan Regency - Rezal Hadi Basalamah; Andi Rahmat Nizar Hidayat; Muhammad Ishak (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study analyzes public communication in collaborative public management for blue economy governance in Pangkajene and Kepulauan Regency, Indonesia. The study responds to the need to understand blue economy development not only as fisheries, aquaculture, tourism, or marine economic growth, but also as a governance process involving coordination, participation, equity, inclusiveness, and accountability. A qualitative field case study was conducted from February to May 2026 in Mattiro Bombang, Mattiro Kanja, and Sabalana Villages. Data were collected through semi-structured interviews, field observations, focus group discussions, and policy documentation involving 29 informants from local government, village governments, fisher groups, aquaculture farmers, coastal women, micro-enterprises, academics, and community leaders. Data were analyzed through thematic coding, data condensation, data display, and conclusion drawing, supported by triangulation, member checking, and informant anonymization. The findings show that local government has established public communication programs, Musrenbang, public consultations, fisher group development, coordination with extension officers, and monitoring mechanisms. However, these instruments require stronger proposal follow-up, wider communication reach, transparent beneficiary selection, and social accountability. Public communication functions as a managerial instrument for information dissemination, dialogue, aspiration absorption, trust building, policy clarification, and feedback. The study proposes the Good Equity and Inclusiveness Collaborative Blue Economy Governance framework as an initial empirically informed framework consisting of island-based diagnosis, inclusive cross-actor forums, a benefit equity matrix, co-production programs, and adaptive accountability. The framework requires further testing, contextual adaptation, and policy validation before operational adoption by local government institutions in practice.